2019
DOI: 10.1167/19.7.6
|View full text |Cite
|
Sign up to set email alerts
|

The face-in-the-crowd effect: Threat detection versus iso-feature suppression and collinear facilitation

Abstract: Are people biologically prepared for the rapid detection of threat posed by an angry facial expression, even when it is conveyed in the form of a schematic line drawing? Based on visual search times, the current literature would suggest that the answer is yes. But are there lowlevel explanations for this effect? Here, we present visual search results for schematic faces using current best practice, based on a concentric search array and set size manipulation. Using this approach, we replicate the classic searc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 57 publications
1
3
0
Order By: Relevance
“…Like Study 2, participants searched for targets defined by their emotional expression that also differed systematically with regards to facial hair (bearded or clean-shaven). As predicted and consistent with past studies, an overall anger superiority effect was observed 12 , 13 . Consistent with Study 1, participants were faster to search through arrays of clean-shaven faces to determine target absence.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Like Study 2, participants searched for targets defined by their emotional expression that also differed systematically with regards to facial hair (bearded or clean-shaven). As predicted and consistent with past studies, an overall anger superiority effect was observed 12 , 13 . Consistent with Study 1, participants were faster to search through arrays of clean-shaven faces to determine target absence.…”
Section: Discussionsupporting
confidence: 92%
“…For example, the face in the crowd effect described how angry expressions are rapidly detected in arrays of faces posing neutral or happy facial expressions due to an evolved pre-attentive threat detection and avoidance system 11 . These findings were replicated in several subsequent studies that renamed the phenomenon—the anger superiority effect 8 , 9 , 12 , 13 .…”
Section: Introductionmentioning
confidence: 65%
“…For instance, Purcell et al (1996) first noted that photographs’ illumination, brightness, and contrast artifacts were to be carefully controlled. The use of schematic faces cannot be the answer ( Coelho et al, 2011 ; Beaudry et al, 2014 ; Watier, 2018 , see also Kennett and Wallis, 2019 for more recent findings) as—beyond violating ecological validity—they also comprise low-level visual features related to the interaction between the lines representing eyebrows and mouth and the surroundings representing the head, forming “T” junctions with the surround. These junctions and differences in line orientation are likely responsible for the search advantage seen in schematic stimuli rather than the “emotions” displayed on the faces.…”
Section: Introductionmentioning
confidence: 99%
“…From an evolutionary point of view, prioritized detection for emotional cues on the faces of others was likely adaptive throughout human evolution as it helped survival by, for instance, foreshadowing danger (angry expression), or promoting trustworthiness (happy expression). Several research fronts are focused on the root causes of visual search advantage related to schematic faces ( Kennett and Wallis, 2019 ), emotional interpretation of Emojis ( Franco and Fugate, 2020 ), or comparing different methods related to happy faces search advantage research ( Rohr et al, 2012 ; Calvo and Beltrán, 2013 ; Wirth and Wentura, 2020 ). However, whether happy or angry emotional facial expressions portray particular features that foster accurate and prompt recognition and detection is still debated (e.g., Calvo and Nummenmaa, 2008 ; Becker and Rheem, 2020 ).…”
Section: Introductionmentioning
confidence: 99%